Patient radiation dose reduction using a commercial iterative reconstruction technique package - Sulieman, A.; Adam, H.; Elnour, A.; Tamam, N.; Alhaili, A.; Alkhorayef, M.; Alghamdi, S.; Khandaker, Mayeen Uddin *; Bradley, D.A. * (Elsevier, 2021)
With 75.4% of the effective doses from imaging estimated to result from computed tomography (CT), it is the leading source of medical radiation. This important observation links with a further estimate that some 2% of all cancers are a result of medical imaging exposures. Acknowledging justification and optimization to be key towards preventing unnecessary radiation exposure, present study aims to investigate radiation exposures reduction for patients undergoing multiphase CT abdomen. Study was made of 111 CT examinations, use being made of two imaging protocols. Of these cases, 55 (49.5%) were obtained using a standard imaging protocol, the remainder being studied using the pure 3D SureExposure™ low-dose technique to obtain a complete abdomen multi-phase examination. Image quality was the subject of blind analysis by two experienced radiologists. For the standard imaging protocol, the mean and standard deviation for CTDIvol and DLP were respectively 7.2 ± 2.3 mGy and 1325 ± 605 mGy cm. For the pure 3D SureExposure™ low-dose technique the respective values were 5.2 ± 1.6 mGy and 812 ± 157 mGy cm. With an achieved mean dose reduction of up to 48%, use of the low dose techniques offers appreciable potential for dose saving without affecting the image quality.